MOVEMENT AND HABITAT USE OF A RESIDENT KING RAIL (Rallus elegans) POPULATION AMONG MANAGED IMPOUNDMENTS AND TIDAL MARSHES IN COASTAL SOUTH CAROLINA - Linke, Megan Michelle (East Carolina University)
Freshwater wetlands are important habitat for a variety of waterbirds. However, inland wetlands have sustained significant losses due to marsh drainage and land conversion for agriculture and human development. This loss of habitat has led to declining populations throughout the Eastern United States for an obligate freshwater marsh specialist, the king rail (Rallus elegans). Loss of inland habitat has pushed king rail populations toward the coastal margins of their range, where they are increasingly exposed to climate change related assaults such as hurricanes and associated storm surge, tidal inundation, and saltwater intrusion. To support habitat restoration and management efforts for a coastal king rail population, I investigated king rail movements and habitat use across a series of natural and impounded wetlands, interspersed with riparian forest along a tidally influenced river in coastal South Carolina. Some impoundments were managed for wintering waterfowl by planting fields with Carolina Gold rice during the king rail breeding season. Using VHF radiotelemetry, 13 king rails were tracked over the course of this two-year study generating Autocorrelated Kernel Density Estimated (AKDEc) home ranges. Breeding season 95% AKDEc was 5.1 ± 2.4 ha with a core 50% AKDEc of 1.1 ± 0.5 ha. Non-breeding season 95% AKDEc was 4.0 ± 2.3 ha with a core home range of 1.0 ± 0.5 ha. No significant difference was observed between the size of the breeding and non-breeding home ranges, and the size of home ranges observed here were smaller than other reported home ranges, suggesting the possibility of high prey and/or high king rail densities. Shifts to distinct non-breeding home ranges were observed between May and July and were preceded by either the successful molting of an instrumented individual’s chicks, nest failure, or habitat disturbance through management within the home range. Individuals that were heavier upon capture were more likely to occupy the same home range throughout the year, staying on the breeding home range for the non-breeding season. During the 2024 breeding season, king rails used habitat closer to channels in areas with higher percentages of marsh vegetation. Dominant vegetation types included giant cutgrass (Zizaniopsis miliacea), smartweeds (Polygonum ssp.), sedges (Carex ssp.), coffeeweed (Sesbania herbacea), and primrose willow (Ludwigia peploides). King rails continued to use areas within their established home range if it had been treated with herbicide, as the dead vegetation likely provided the same habitat characteristics as it did when it was alive, and the rails were already established in the area. A stem count measurement revealed that king rails avoided the densest marsh vegetation and selected areas with more moderate densities. My results suggest that when managing impoundments for king rails alongside wintering waterfowl, it is important to provide vegetation along channels and irrigation ditches within rice fields to provide cover while king rails forage along the edges of the channels. The removal of vegetation when planting rice and during dike construction reduced the likelihood for king rails to stay on their breeding territories and resulted in some individuals fleeing the area. Management techniques to control the density of emergent vegetation such as prescribed fire may be useful to keep a moderate density on the landscape.
Keywords: Biology, Ecology